The many characters of visual alpha oscillations - Clayton, Michael S.; Yeung, Nick; Cohen Kadosh, Roi (The European journal of neuroscience, 2018)
A central feature of human brain activity is the alpha rhythm: a 7–13 Hz oscillation observed most notably over occipitoparietal brain regions during periods of eyes‐closed rest. Alpha oscillations covary with changes in visual processing and have been associated with a broad range of neurocognitive functions. In this article, we review these associations and suggest that alpha oscillations can be thought to exhibit at least five distinct ‘characters’: those of the inhibitor, perceiver, predictor, communicator and stabiliser. In short, while alpha oscillations are strongly associated with reductions in visual attention, they also appear to play important roles in regulating the timing and temporal resolution of perception. Furthermore, alpha oscillations are strongly associated with top‐down control and may facilitate transmission of predictions to visual cortex. This is in addition to promoting communication between frontal and posterior brain regions more generally, as well as maintaining ongoing perceptual states. We discuss why alpha oscillations might associate with such a broad range of cognitive functions and suggest ways in which these diverse associations can be studied experimentally. Alpha oscillations in posterior cortex are one of the most dominant rhythms of the human brain. Although classically associated with reductions in visual processing, recent evidence has suggested that these oscillations contribute to a diverse range of cognitive functions. In this article, we review this evidence and suggest that visual alpha oscillations exhibit at least five distinct ‘characters’: those of the inhibitor, perceiver, predictor, communicator and stabiliser.